2020
DOI: 10.3102/0002831220954431
|View full text |Cite
|
Sign up to set email alerts
|

Remembering and Revisiting Pedagogies of the Home

Abstract: Almost two decades after Delgado Bernal’s theorization of pedagogies of the home, this article examines pedagogies of the home of four Chicana/o college-educated families to understand the role of parent engagement not only in the college choice processes but also in college completion and graduate school enrollment. Using Chicana feminisms to inform educational oral histories, four Chicana/o parent-child dyads were interviewed. The findings suggest that among Chicana/o college-educated families the (re)making… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…Further, these participants were able to reactivate their resilient resistance in college, underscored by practices associated with help-seeking behaviors, cultivating race-, class-, and gender-based affinity groups, and utilizing cultural knowledge to reaffirm their expectations through internal and group accountability (Delgado Bernal, 2001;Garcia & Delgado Bernal, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Further, these participants were able to reactivate their resilient resistance in college, underscored by practices associated with help-seeking behaviors, cultivating race-, class-, and gender-based affinity groups, and utilizing cultural knowledge to reaffirm their expectations through internal and group accountability (Delgado Bernal, 2001;Garcia & Delgado Bernal, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Similar to Villenas and Moreno’s (2001) findings on immigrant mothers, the mother-daughter pedagogies of Latina mothers were “narrated and discursively practiced, embodied, improvised, and contested” to, at times, reify patriarchal gendered beliefs and practices, while sometimes simultaneously disrupting those beliefs and practices (p. 685). Our fathers, despite being college educated, contradicted their practices and beliefs to consciously or unconsciously disrupt and reify gendered practices (Garcia & Delgado Bernal, 2019).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…They were met with rebellious acts and enforced strict discipline to maintain our behavior. Garcia and Delgado Bernal (2019) found that (re)covering tensions ''confronts the messy, often contradicting, and nuanced pedagogies that unfold within the home of origin that occur due to varying raced-gendered experiences among Chicana/o college-educated dyads'' (p. 18). Further, they also found that (re)covering of tension occurred through emotion, memories, and contradictions between Chicana daughters and their parents.…”
Section: Garcia Mireles-riosmentioning
confidence: 99%
“…To rethink traditional notions of what counts as knowledge, critical racedgendered epistemologies acknowledge that the life experiences of persons are unique and individual, while at the same time both collective and connected (Bernal, 2002;Garcia & Mireles-Rios, 2020). Other scholars have theorized experiential knowledge as pedagogies of home as a way to embrace knowledges taught within the household; however, these teachings continue to go unrecognized by schools (Garcia & Delgado Bernal, 2020).…”
Section: Using Narrative To Move Communication Towards a Two-way Dial...mentioning
confidence: 99%
“…67-68). Therefore, as foundational to my research processes, I drew on my cultural intuition to co-create cultural knowledges informed by my personal and professional experiences (Garcia & Delgado Bernal, 2020). This meant that by cultivating reciprocal trusting relationships with Latinx mothers of children with dis/abilities, I was building on community knowledge that was shared among Latinx families through various modes of storytelling, behavior, and scholarship (Garcia & Mireles-Rios, 2020).…”
Section: Los Cuentos: Mothers Sharing Their Oral Historiesmentioning
confidence: 99%